The clinical relevance of dupilumab serum concentration in patients with atopic dermatitis: a two-center prospective cohort study - Angela L. Bosma; Louise A. A. Gerbens; Hajar El Khattabi; Floris C. Loeff; Michael Duckworth; Richard T. Woolf; Theo Rispens; Catherine H. Smith; Phyllis I. Spuls (Taylor & Francis Group, 2023)
Background Dupilumab is prescribed in one dosage across adult atopic dermatitis patients. Differences in drug exposure may explain variation in treatment response. Objective Investigating the clinical relevance of dupilumab serum concentration in atopic dermatitis in real-world practice. Methods In two centers (Netherlands, UK), adults treated with dupilumab for atopic dermatitis were evaluated for effectiveness and safety pretreatment and at 2, 12, 24, and 48 weeks; trough serum samples were analyzed for dupilumab concentration at corresponding time points. Results In 149 patients, median dupilumab levels during follow-up ranged from 57.4 to 72.4 μg/mL. Levels showed high inter-patient and low intra-patient variability. No correlation was found between levels and ΔEASI. At 2 weeks, levels of ≥64.1 μg/mL predict EASI ≤7 at 24 weeks (specificity:100%, sensitivity:60%; p = .022). At 12 weeks, ≤32.7 μg/mL predicts EASI >7 at 24 weeks (sensitivity:95%, specificity:26%; p = .011). Inverse correlations were found between baseline EASI and levels at 2, 12, and 24 weeks (r = −0.25 to 0.36; p ≤ .023). Low levels were particularly observed in patients with adverse events, treatment interval deviation, and discontinuation. Conclusion At the on-label dosage, the measured range of dupilumab levels does not seem to yield differences in treatment effectiveness. However, disease activity does seem to influence dupilumab levels - higher baseline disease activity results in lower levels at follow-up.